2021
DOI: 10.1371/journal.pone.0247238
|View full text |Cite
|
Sign up to set email alerts
|

Developing an enhanced 7-color multiplex IHC protocol to dissect immune infiltration in human cancers

Abstract: The TSA Opal multiplex immunohistochemistry (mIHC) protocol (PerkinElmer) has been used to characterize immune infiltration in human cancers. This technique allows multiple biomarkers to be simultaneously stained in a single tissue section, which helps to elucidate the spatial relationship among individual cell types. We developed and optimized two improved mIHC protocols for a 7-color panel containing 6 biomarkers (CD3, CD8, CD163, PD-L1, FoxP3, and cytokeratin (CK)) and DAPI. The only difference between thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 32 publications
(16 reference statements)
0
16
0
Order By: Relevance
“…Since immune cells require multiple markers for lineage and phenotype identification, quantitative evaluation of immune cell lineages with spatial information has been technically challenging due to the limited number of analyzable markers in conventional IHC and immunofluorescence methodologies. To tackle those grand challenges, a variety of new approaches have been actively developed in the field of head and neck cancer as well as various malignancies via seminal technologies such as NanoString GeoMx digital spatial profiling (24), Vectra Polaris ( 16), co-detection by indexing (25), Visium spatial gene expression analysis (26) and other mIHC technologies (12,27,28). Owing to recent advances in multiplex IHC and immunofluorescence technologies as well as spatial genomics and molecular imaging technologies, we adopted a 12-marker chromogenic multiplex IHC platform with tissue segmentation algorithms, enabling identification of cellular components with preserved tissue architecture (Figures 1B-D).…”
Section: Discussionmentioning
confidence: 99%
“…Since immune cells require multiple markers for lineage and phenotype identification, quantitative evaluation of immune cell lineages with spatial information has been technically challenging due to the limited number of analyzable markers in conventional IHC and immunofluorescence methodologies. To tackle those grand challenges, a variety of new approaches have been actively developed in the field of head and neck cancer as well as various malignancies via seminal technologies such as NanoString GeoMx digital spatial profiling (24), Vectra Polaris ( 16), co-detection by indexing (25), Visium spatial gene expression analysis (26) and other mIHC technologies (12,27,28). Owing to recent advances in multiplex IHC and immunofluorescence technologies as well as spatial genomics and molecular imaging technologies, we adopted a 12-marker chromogenic multiplex IHC platform with tissue segmentation algorithms, enabling identification of cellular components with preserved tissue architecture (Figures 1B-D).…”
Section: Discussionmentioning
confidence: 99%
“…mIHC takes advantage of multiple cycles of staining and antibody stripping to allow detection of multiple markers on a single tissue section, thereby overcoming the limitation of standard chromogenic IHC. Despite the effectiveness and reliability of mIHC in simultaneously detecting several markers, most of the published mIHC protocols have been optimised for human FFPE specimens [5,31,32]. Since preclinical mouse models are indispensable in translational research, we sought to optimise a protocol and mIHC workflow for mouse FFPE tissue to characterise the immune microenvironment in intestinal disease and cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Immersion of tumor immune cells as an important part of the tumor microenvironment, and cancer closely related to the occurrence and development of or transfer [20][21][22]. We found that using the TIDE algorithm in the database, SNRPC was found to be related to the inhibition of immune cells from myelin sources of many tumors.…”
Section: The Potential Relationship Among the Immersion Levels Of Different Immune Cells With The Expression Of The Snrpc Gene Of Differementioning
confidence: 99%